The Making of Middle Indonesia - van Klinken, G. (Power and Place in Southeast Asia, 2014)
What holds Indonesia together? In The Making of Middle Indonesia, Gerry van Klinken develops an innovative historical explanation that looks beyond national elites to middle classes in provincial towns.